2002
DOI: 10.1590/s1519-566x2002000400013
|View full text |Cite
|
Sign up to set email alerts
|

Extração de Alimento por Cosmoclopius nigroannulatus Stål (Hemiptera: Reduviidae) de Ninfas de Spartocera dentiventris (Berg) (Hemiptera: Coreidae)

Abstract: -The food extraction by Cosmoclopius nigroannulatus Stål from first-instar nymphs of Spartocera dentiventris (Berg) was evaluated. The experiment was conducted in laboratory. Ten newly emerged and individualized adults of each sex were used, for each of the five quantities of prey tested (5.1; 14.7; 29.8; 36.6; 44.8 mg, for males and 5.5; 14.7; 31.1; 37.4; 48.5 mg for females). During five days, the weight of the adults, the total amount of nymphs consumed and the weight of the remaining nymphs, the time spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
1
5
0
6
Order By: Relevance
“…1). Rocha et al (2002) also found similar results, showing an increase in the amount of food consumed and a decrease in the percentage of prey consumed by the females of Cosmoclopius nigroannulatus (Stal) (Hemiptera: Reduviidae) as the density of nymphs Spartocera dentiventris (Berg) (Hemiptera: Coreidae) from the 1st instar increased. According to Mukerji and LeRoux (1969), the increase in daily consumption of nymphs of P. maculiventris was proportional to the amount of prey available.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…1). Rocha et al (2002) also found similar results, showing an increase in the amount of food consumed and a decrease in the percentage of prey consumed by the females of Cosmoclopius nigroannulatus (Stal) (Hemiptera: Reduviidae) as the density of nymphs Spartocera dentiventris (Berg) (Hemiptera: Coreidae) from the 1st instar increased. According to Mukerji and LeRoux (1969), the increase in daily consumption of nymphs of P. maculiventris was proportional to the amount of prey available.…”
Section: Resultssupporting
confidence: 59%
“…The effect of the prey density on the percentage of prey consumed by P. nigrispinus males depended of the adult age (F (age x density) = 3.98; P= 0.05) ( Table 2). Predator age also affected the consumption rates of predator C. nigroannulatus between their first and fifth days of life (Rocha et al, 2002). This could be due to physiological changes, and therefore, it was not dependent on the quantity of food consumed (Morris, 1963).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…has also been observed by Silva et al (1968). Rocha (2002), in study on the food extraction from S. dentiventris nymphs by C. nigroannulatus, concluded that the reduvid can be considered a eficient predator on nymphs, showing a high potential as a biological control agent on tobacco crops.…”
Section: Resultsmentioning
confidence: 99%
“…Casual observations in the field indicated the presence of the predator Cosmoclopius nigroannulatus Stål (Heteroptera: Reduviidae) in high numbers in the system. Population dynamics and the funcional response of this reduvid were the focuses of the works of Jahnke et al (2002) and Rocha (2002), respectively. This knowledge is adding to build a very detailed picture of the system, which will eventually allow a well fundamented theoretichal analysis.…”
mentioning
confidence: 99%